The Effect on the Birth Process of Endogenous Oxytocin Release Via Coitus at Home in Pregnant Women in the Latent Phase - Kurt, Begum; Demirel, Gulbahtiyar; Caglayan, Ilkin Seda; Doganer, Adem (Zeitschrift für Geburtshilfe und Neonatologie, 2023)
Objectives This study was conducted to determine the effect of endogenous oxytocin release via coitus at home on the delivery process in pregnant women who were not hospitalized in the latent phase.Background For healthy pregnant women who can deliver spontaneously, it is recommended to be admitted to the delivery room during the active phase of labor. When the pregnant woman is admitted to the delivery room in the latent phase before the active stage, pregnant women spend more time in the delivery room, which makes medical intervention inevitable.Methods 112 pregnant women for whom hospitalization in the latent phase was recommended were included in the randomized controlled study. They were divided into two groups in which sexual activity in the latent phase was recommended (n=56) and the control group (n=56).Results In our study, the duration of the 1st stage of labor was found to be significantly shorter in the group in which sexual activity in the latent phase was recommended, compared to the control group (p=0.001). Again, the need for amniotomy, labor induction with oxytocin, analgesics and episiotomy decreased.Conclusion Sexual activity can be considered as a natural way to speed up labor, reduce medical interventions, and prevent postterm pregnancy.
Keywords: birth process; endogenous oxytocin; coitus; latent phase; pregnancy